Quinoa–Olive Agroforestry System Assessment in Semi-Arid Environments: Performance of an Innovative System - Ilham Abidi; Khalid Daoui; Aziz Abouabdillah; Loubna Belqadi; Hamid Mahyou; Didier Bazile; Ahmed Douaik; Fatima Gaboun; Abdel Aziz Hassane Sidikou; Si Bennasseur Alaoui (Agronomy, 2024)
Agroforestry is a promising way to sustain land use efficiency in semi-arid areas. In this study, we introduce quinoa as a drought- and salinity-tolerant crop in olive-based agroforestry. We investigated how the microclimate created by olive trees affects agronomic and biochemical traits in quinoa and evaluated the performance of this new olive-based agroforestry system in terms of land equivalent ratio (LER). Field experiments were carried out under two pedoclimatic conditions (S1) and (S2) using a randomized complete block design with two cropping systems (sole crop (SCS) and agroforestry (AFS) systems), four quinoa cultivars (Puno, Titicaca, ICBA-Q5, and ICBA-Q4) and one olive orchard as a control (OR) in each block. Our results show that AFS had lower grain yield (−45%), dry biomass (−49%), and crop water productivity (−44%), but higher plant height (12%), grain protein (4%), saponin (26%), total polyphenol (12%), and DPPH (9%) contents compared to SCS. The highest grain yield was recorded for Titicaca and ICBA-Q5 (1.6 t ha−1). The LER ranged from 1.57 to 2.07, indicating that the overall productivity was 57% to 107% higher in the agroforestry system compared with the monoculture. We suggest that quinoa–olive tree intercropping could be a promising agroecological practice under semi-arid conditions.